Process safety management and process hazard analysis implementation progress in Pakistan chemical process industries - Rashid, M.I. (John Wiley and Sons Inc, 2022)
Pakistan is a developing country and has various chemical process industries to fulfill the local demands of numerous chemical products. In order to maintain the uninterrupted production from these industries, safety protocols need to be implemented. Safety progress must be studied with passage of time to identify the gaps and to decide the future actions. In this article, process safety in various chemical process industries (CPIs) of Pakistan is investigated regarding process safety management (PSM) and process hazard analysis (PHA). The covered industries include mainly fertilizer complexes, food processing plants, gas and oil processing plants, oil refineries, petrochemical plants, polymer processing plants, paper industries, tire industries, and sugar industries. This research will help in addressing the weaknesses. A comparative analysis of all considered CPIs is provided graphically. Overall analysis of all industries depicts that more emphasis on three categories is required, namely (1) documents upgradation and staff communication, (2) PHA revision and auditing, (3) PHA recommendations documentation and implementation. Provided suggestions, the implementation of PSM and PHA in Pakistan CPIs is expected to enhance, which may lead to a substantial increase in productivity of these industries without accidents. Â© 2021 American Institute of Chemical Engineers.